ANALISIS POTENSI EKONOMI KABUPATEN SUMBAWA TAHUN 2016-2021 - Fitri Handayani; S Syafruddin; Binar Dwiyanto Pamungkas (Pusat Riset dan Publikasi, 2023)
This study aims to determine the potential of the economic sector which can be used as a base or superior economic sector in Sumbawa Regency District. This study used a descriptive method with the type of data used was quantitative data in the form of Gross Regional Domestic Product of Sumbawa District data for 2016-2021 from all existing economic sectors. This data was obtained from published documents or archives of the Sumbawa District Central Statistics Agency. The data analysis tool used was the analysis technique of location quotient (LQ) analysis, shift share analysis, and klassen typological Analysis. Based on the results of the LQ analysis, it shows that there are seven economic sectors in Sumbawa Regency which have an LQ value greater than 1 (>1) so that they can be used as base or superior sectors in Sumbawa District, but there are only four economic sectors in Sumbawa District those in quadrant I, namely sectors that are relatively advanced and growing rapidly (developed sectors), are the agriculture, forestry and fisheries sectors; electricity and gas procurement sector; wholesale and retail trade sector, car and motorbike repair; and the government administration, defense and mandatory social security sectors. These sectors have a very large contribution in forming Sumbawa District GRDP and if managed well these sectors will continue to be growing sectors in the future.